Regulating the night: race, culture and exclusion in the making of the night-time economy - Talbot, Deborah (Re-materialising cultural geography, 2007)
Nightlife and outsider areas in an era of spatial and subcultural closure: recasting the politics of popular culture -- Negotiating research into the regulation of outsider areas -- The growth, criminalisation and decline of unregulated night spaces in Southview -- Urban regeneration, conflict and change -- From nightlife to the night-time economy -- Licensing and the loss of political and moral authority -- Licensing, policing and the informal mechanics of exclusion